Divinity in Henry Bergson’s philosophy: A critical study - Al-harby, Dalal Saeed (Journal of Humanities & Social Sciences, 2022)
This study aimed to reveal the falsity of Bergsonian philosophy and its deviant beliefs about divinity, to preserve faith, protect monotheism, and purify Islamic thoughts through three main topics. The first topic reviews the definition of the most important factors that shaped Henry Bergson’s philosophy; his life, his scientific upbringing, and the development of his philosophy (philosophy of life). Also, the first topic will discuss the status and influence of Bergsonism in the history of Western and Arab philosophy. The second topic presents the principles of Bergsonian philosophy on divinity, by addressing “divinity and creation” and “divinity and superstition” through two sources: morality and religion. Then, the second topic discusses the divinity and knowledge sources in Bergson’s philosophy. The third topic presents Islam attitude towards Bergsonian philosophy, analysis that philosophy and criticize it, and arguing it depending on the reality of its philosophers and Islam thoughts. This study used the descriptive and analytical approaches to achieve its objectives. The findings of this study included: Any wiliness would lead to the destruction of humanity look for the Jewish fingers behind it. Bergson has failed to reach the spiritual truth; since it places the soul and body against each other, and does not realize that the differentiation of the soul and body does not necessitate their separation. The independence in existence and action cannot be issued without the participation of the body. The idea of creative evolution is contradictory, does not depend on the argument, and cannot be undermined by argument.